Adherence to New Zealand's Major Trauma Destination Policy: An Audit of Current Practice - Gibson, G; Dicker, B; Civil, I; Kool, B (Pasifika Medical Association Group, 2024)
AIM: To evaluate adherence to the New Zealand Major Trauma Destination Policy (MTDP). This audit assessed if, based on their injuries, Emergency Medical Services (EMS) attended major trauma cases were taken to the MTDP determined appropriate hospital. Findings will guide and further improve pre-hospital trauma care and associated patient outcomes. METHODS: A retrospective evaluation of adherence to the New Zealand MTDP for a random sample of 100 cases (ISS >12) injured between 31 November 2017-30 November 2018 who survived to hospital. The EMS electronic patient record (ePRF) was reviewed for each case. Adherence was indicated by the transport of injured patients from the scene to the appropriate initial destination based on meeting the respective regional MTDPs. RESULTS: Overall, there was a 94% adherence rate to the MTDP. For patients that were not classified as requiring transport to an advanced-level trauma centre, there was a 98.9% (n=86/87) adherence compared to 61.5% (n=8/13) adherence in those that did require transport to an advanced-level trauma centre. CONCLUSION: There was high adherence to the MTDP, with 94% of cases being taken to the appropriate destination directly from the incident scene. There is scope for improvement in cases whereby the nearest hospital should be bypassed in favour of a more distant advanced-level trauma centre.
Keywords: 32 Biomedical and Clinical Sciences; 3202 Clinical Sciences; 42 Health Sciences; Physical Injury - Accidents and Adverse Effects; Emergency Care; Injuries and accidents; 3 Good Health and Well Being; 11 Medical and Health Sciences; General & Internal Medicine; 32 Biomedical and clinical sciences; 42 Health sciences; Humans; New Zealand; Retrospective Studies; Guideline Adherence; Male; Female; Trauma Centers; Adult; Middle Aged; Wounds and Injuries; Emergency Medical Services; Aged; Medical Audit; Young Adult; Transportation of Patients; Humans; Wounds and Injuries; Transportation of Patients; Retrospective Studies; Adult; Aged; Middle Aged; Trauma Centers; Emergency Medical Services; Guideline Adherence; Medical Audit; New Zealand; Female; Male; Young Adult; Humans; New Zealand; Retrospective Studies; Guideline Adherence; Male; Female; Trauma Centers; Adult; Middle Aged; Wounds and Injuries; Emergency Medical Services; Aged; Medical Audit; Young Adult; Transportation of Patients